2021
DOI: 10.20944/preprints202107.0034.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proof of Gene Doping in a Mouse Model with a Human Erythropoietin Gene Transferred Using an Adenoviral Vector

Abstract: The World Anti-Doping Agency (WADA) has prohibited gene doping in the context of progress in gene therapy. In addition, there is a risk of the EPO gene being applied in gene doping among athletes. Along with this, development of a gene-doping test has been underway in worldwide. Here, we had two purposes: to develop a robust gene doping mouse model using the human EPO gene (hEPO) transferred using recombinant adenovirus (rAdV) as a vector and to develop a detection method to prove gene doping using this model.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…In January 2021, WADA released laboratory guidelines regarding gene doping detection methods employing polymerase chain reaction (PCR), 150 and several studies elaborating on currently available models and analytical approaches for detecting transgenes for sports drug testing purposes as well as strengths and limitations were published 112 . For instance, Sugasawa et al 113 reported on the development of a mouse model transfected with a human EPO gene through an adenoviral vector, which allowed for assessing options of direct (transgene‐focused) and indirect (longitudinal monitoring of RNA expressions) anti‐doping testing strategies. Mice subjected to injections with human EPO‐gene‐containing adenoviral vectors (rAdV‐hEPO) showed significantly increased red blood cell counts and elevated hematopoietic marker gene expressions, indicating the successful gene transfer.…”
Section: Gene Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…In January 2021, WADA released laboratory guidelines regarding gene doping detection methods employing polymerase chain reaction (PCR), 150 and several studies elaborating on currently available models and analytical approaches for detecting transgenes for sports drug testing purposes as well as strengths and limitations were published 112 . For instance, Sugasawa et al 113 reported on the development of a mouse model transfected with a human EPO gene through an adenoviral vector, which allowed for assessing options of direct (transgene‐focused) and indirect (longitudinal monitoring of RNA expressions) anti‐doping testing strategies. Mice subjected to injections with human EPO‐gene‐containing adenoviral vectors (rAdV‐hEPO) showed significantly increased red blood cell counts and elevated hematopoietic marker gene expressions, indicating the successful gene transfer.…”
Section: Gene Dopingmentioning
confidence: 99%
“…109 An important aspect of the applicability of the hematological ABP (PCR), 150 and several studies elaborating on currently available models and analytical approaches for detecting transgenes for sports drug testing purposes as well as strengths and limitations were published. 112 For instance, Sugasawa et al 113 reported on the development of a mouse model transfected with a human EPO gene through an adenoviral vector, which allowed for assessing options of direct…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%